FAKTOR - FAKTOR PENGHAMBAT PENGATURAN PEDAGANG KAKI LIMA BERDASARKAN PERATURAN DAERAH NOMOR 3 TAHUN 2008 (STUDI KASUS di TAMAN POCI dan JALAN PANCASILA) - Kurniawan, Indra; Taufiq, Ahmad; Martini, Rina (Journal of Politic and Government Studies, 2013)
The development of an increasingly complex society trigger problems such as employment issues are minimal and inadequate as the population is increasing , consequently people competing for work with any media for survival , as an example of the phenomenon of the above problems is the existence of street vendors ( Street Vendor ) that mushroomed in big cities is the goal of the people to look for work . Therefore , the City of Tegal make local regulation No. 3 of 2008, which contains the settings hawkers in Tegal .The purpose of this study is to investigate the implementation of Regulation 3 of 2008 on regulation of street vendors in the city of Tegal . To explain the implementation of local regulations No. 3 of 2008 used a descriptive - qualitative method . The data was collected using interview techniques , observation and literature review .